Abbasids, Geray, Golden Horde, Crimean Khanate, Crimean Tatar literature, narrative source, chronicle - Leylya Seytkhalilova; Arzy Alieva (Крымское историческое обозрение)
The given article analyzes the material contained in the essay of the English traveler Mary Holderness “Notes relating to the Manners and Customs of the Crim Tartars” as a part of work published in London in 1823 based on the results of her travels across the Russian Federation. In 1816, Mary Holderness made a trip to the Crimea, where for four years until 1820 she lived in the village of Karagoss in the Crimea.